The Meanings of Publication in Open Access Journal: Experience of State Islamic University's Lecturers - Ida Farida; Prisinta Wanastri; Melinda Lusyyana; Pungki Purnomo (Insaniyat : Journal of Islam and Humanities, 2022)
The Indonesian Ministry of Research, Technology, and Higher Education always encourages lecturers to publish their scientific works in open access publications. This study explores the meaning of open access publications from the experiences of UIN lecturers. This study uses a qualitative method with a phenomenological approach to identify the interpretation and meaning of lecturers on open access journal publications. This study found that lecturers know about publishing in open access journals and their advantages. They choose reputable journals in their scientific field as their first reference because the journals that fall into this category have a high level of readability and citation. However, the informants stated that they were also pragmatic; they will reconsider the decision to publish in a reputable and open access journal if the publication fee is deemed too expensive. This study uses Hall's meanings concept, whose application is not only to explore the views of lecturers on open access publications but also to explore the actions they take so that their writings can be included in open access publications. Here, the researcher finds the emerging theme that is the importance of collaboration. It is as a way to overcome barriers to open access publishing and also as the key to the productivity of writing articles in academic journals. This study highlights several important themes related to collaboration. The integration of Islamic knowledge with scientific disciplines is an interesting issue when discussing the benefits of cooperation. The results of this study can provide insight into the meaning of open access journals published by lecturers and how they overcome the barriers in this matter. The researcher suggests using a quantitative approach based on our data for future research.